2021
DOI: 10.1177/20597002211018049
|View full text |Cite
|
Sign up to set email alerts
|

Patients with chronic mild or moderate traumatic brain injury have abnormal longitudinal brain volume enlargement more than atrophy

Abstract: Introduction Many studies have found brain atrophy in patients with traumatic brain injury (TBI), but most of those studies examined patients with moderate or severe TBI. A few recent studies in patients with chronic mild or moderate TBI found abnormally large brain volume. Some of these studies used NeuroQuant®, FDA-cleared software for measuring MRI brain volume. It is not known if the abnormal enlargement occurs before or after injury. The purpose of the current study was to test the hypothesis that it occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 70 publications
(166 reference statements)
0
14
0
Order By: Relevance
“…On 02/19/2022, searches were conducted using the term "NeuroQuant" on PubMed (including cross-referenced articles), Google and Google Scholar. 102 published peer-reviewed studies (described below) were identified that supported the reliability and validity of NeuroQuant R for measuring brain volume in neuropsychiatric patients and normal control subjects (see Figure 1) (Brewer, 2009;Brewer et al, 2009;Kovacevic et al, 2009;Brewer, 2010, 2012;Heister et al, 2011;Engedal et al, 2012;Farid et al, 2012;Hampstead et al, 2012Hampstead et al, , 2016Moen et al, 2012;Ross et al, 2012aRoss et al, ,b, 2013aRoss et al, ,b,c, 2014Ross et al, , 2015Ross et al, , 2016Ross et al, , 2018aRoss et al, ,b, 2020Ross et al, , 2021Bahar-Fuchs et al, 2013;Desikan et al, 2013;Hampstead and Brown, 2013;Ong et al, 2013;Rogne et al, 2013Rogne et al, , 2016Brezova et al, 2014;Elvemo et al, 2014Elvemo et al, , 2015England et al, 2014;Evans et al, 2014;Hill et al, 2014;Kjelvik et al, 2014;Okamura et al, 2014;Shoemaker et al, 2014;Ting et al, 2014;Villemagne et al, 2014Villemagne et al, , 2017Yaldizli et al, 2014;Yu et al, 2014;…”
Section: Literature Reviewmentioning
confidence: 97%
See 4 more Smart Citations
“…On 02/19/2022, searches were conducted using the term "NeuroQuant" on PubMed (including cross-referenced articles), Google and Google Scholar. 102 published peer-reviewed studies (described below) were identified that supported the reliability and validity of NeuroQuant R for measuring brain volume in neuropsychiatric patients and normal control subjects (see Figure 1) (Brewer, 2009;Brewer et al, 2009;Kovacevic et al, 2009;Brewer, 2010, 2012;Heister et al, 2011;Engedal et al, 2012;Farid et al, 2012;Hampstead et al, 2012Hampstead et al, , 2016Moen et al, 2012;Ross et al, 2012aRoss et al, ,b, 2013aRoss et al, ,b,c, 2014Ross et al, , 2015Ross et al, , 2016Ross et al, , 2018aRoss et al, ,b, 2020Ross et al, , 2021Bahar-Fuchs et al, 2013;Desikan et al, 2013;Hampstead and Brown, 2013;Ong et al, 2013;Rogne et al, 2013Rogne et al, , 2016Brezova et al, 2014;Elvemo et al, 2014Elvemo et al, , 2015England et al, 2014;Evans et al, 2014;Hill et al, 2014;Kjelvik et al, 2014;Okamura et al, 2014;Shoemaker et al, 2014;Ting et al, 2014;Villemagne et al, 2014Villemagne et al, , 2017Yaldizli et al, 2014;Yu et al, 2014;…”
Section: Literature Reviewmentioning
confidence: 97%
“…NeuroGage R 2.0 was similar to NeuroGage R 1.0 insofar as it continued to provide analyses for asymmetry, longitudinal change and volume estimation (Ross et al, 2018b(Ross et al, , 2021. However, it was improved in several ways: (1) it was based on NeuroQuant R 2.0 analyses instead of 1.0 analyses; (2) it included more brain regions than NeuroGage R 1.0; (3) it included more normal controls (N = 80); and (4) and for determination of the normal relationship between brain volume vs. age across the adult lifespan, it used NeuroQuant R normal control data (N = approximately 4000) instead of data from a previously published meta-analysis of normal control studies that in total had less normal controls (N = 2,211) and that used various volumetric software programs other than NeuroQuant R (Hedman et al, 2012).…”
Section: Evolution Of Neuroquant R and Neurogage Rmentioning
confidence: 99%
See 3 more Smart Citations